Opening characteristics of high current fast switch for DC circuit breaker - LAN Jian; FENG Ying; WANG Chengyu (电力工程技术, 2023)
The stability of opening process of fast mechanical switch is the key factor affecting the breaking performance of DC circuit breaker. Based on the finite element method, the multi-field coupling calculation of electromagnetic, thermal and momentum is carried out for the opening process of high current fast switch with permanent magnet operating mechanism and electromagnetic repulsion mechanism. The influence of the driving coil input for the permanent magnet operating mechanism and different driving coil currents on the opening process of double-action mechanism are analyzed. The calculation results show that the permanent magnet suction force can be cancelled in advance when the driving coil of the permanent magnet operating mechanism is put in, thereby avoiding the opening spring back phenomenon caused by the electromagnetic repulsion force due to the short working time. Because the electromagnetic repulsion force is very large at the initial stage of opening, the driving coil input of the permanent magnet operating mechanism has little influence on the initial speed of opening. After the electromagnetic repulsion disappears, the greater the driving coil current of the permanent magnet operating mechanism is, the greater the speed to reach the rated opening distance after the electromagnetic repulsion force disappearing. In order to avoid opening rebound phenomenon, the current value of the driving coil should be selected reasonably. The comparison between the simulation results and the opening process characteristic curves of the actual prototype shows that two curves are in good agreement, which verifies the correctness of the simulation method.